Qualidade de vida e capacidade funcional em pacientes com doenças inflamatórias intestinais - Dallaqua, Renata Pighinelli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: Inflammatory bowel diseases (IBD) are multifactorial etiology, chronic diseases. The most current manifestations are ulcerative colitis (UC) and Crohn's disease (CD). The intensity and chronical factor of these diseases may affect negatively one's daily life and interfere in the quality of life (QoL) and functional ability (FA) of patients. Purpose: To assess QoL and FA in patients with IBD, and to study relationship of QoL and FA indicators with social and demographic, clinical, and psychosocial variables (symptoms of anxiety and depression, social support, illness perception). Method: Cross-sectional, descriptive and analytical study. The sampling of this research was of 106 patients, 53 with CD and 53 with UC, who were treated at a IBD outpatient clinic in Botucatu College of Medicine Medical Hospital. The sampling was calculated in order to achieve differences of 20%, approximately, with a 5% significance level and 80% power. Several scores and tests were utilized, such as a standardized form for social, demographic and clinical data acquisition; the Mayo score and the Crohn's Disease Activity Index (CDAI) for assessment of UC and CD clinical activity, respectively. Anxiety and depression symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS). The Medical Outcomes Study 36 Item Short-Form Health Survey (SF-36) and the Inflammatory Bowel Disease Questionnaire (IBDQ) were utilized in order to assess quality of life. Functional activity and illness perception were assessed using the Karnofsky Score and the Brief Illness Perception Questionnaire (B-IPQ), respectively. Data were evaluated by bivariate and multivariate, descriptive statistical analysis, and quality of life and functional ability indicators were the main outcomes. Pearson's chi square test were utilized in order to study the relationship between those outcomes and the category variables. Mann-Whitney U Test and Kruskal Wallis Test ...

Introdução: As doenças inflamatórias intestinais (DII) são doenças crônicas, de etiologia multifatorial, sendo as manifestações mais frequentes a Retocolite Ulcerativa (RCU) e a Doença de Crohn (DC). A intensidade e cronicidade dessas doenças podem afetar negativamente a vida diária e interferir na qualidade de vida (QV) e capacidade funcional (CF) de seus portadores. Objetivos: Avaliar QV e CF em pacientes com DII e estudar as associações dos índices de QV e dos índices de CF com variáveis sociodemográficas, clínicas, e psicossociais (sintomas de ansiedade e depressão, apoio, social, percepção da doença). Método: Estudo descritivo e analítico, de corte transversal. A amostra desta pesquisa, calculada para se obterem diferenças da ordem de 20% com um nível de significância de 5% e um poder de teste de 80%, foi de 106 pacientes, 53 com DC e 53 com RCU,atendidos no ambulatório de DII do Hospital das Clínicas de Botucatu da Faculdade de Medicina de Botucatu (HCFMB). Foram utilizados: formulário padronizado para obtenção de dados sociodemográficos e clínicos; Escore de Mayo e Índice de Atividade da Doença de Crohn (CDAI) para avaliação da atividade clínica da RCU e DC, respectivamente. Sintomas depressivos e ansiosos foram avaliados pela Escala Hospitalar de Ansiedade e Depressão (HAD). Para avaliação da qualidade de vida foram aplicados o Questionário Genérico de Avaliação de Qualidade de Vida - Medical Outcomes Study 36 Item Short-Form Health Survey (SF-36) e o Inflammatory Bowel Disease Questionnaire (IBDQ). A capacidade funcional e percepção da doença foram avaliadas pela Escala de Karnofsky e Questionário de Percepção de Doenças Breve (B-IPQ) respectivamente. Os dados foram submetidos à análise estatística descritiva, bivariada e multivariada, tendo como desfechos os índices de qualidade de vida e da capacidade funcional. Para estudar a associação entre esses desfechos com as...
Quality of life and funcional ability in patients with inflamatory bowel disease
Keywords: Doenças inflamatórias intestinais; Incapacidade - Avaliação; Qualidade de vida; Aptidão física; Ansiedade; Estudos transversais; Saúde pública; Pacientes - Pesquisa; Inflammatory bowel deseases; Physical fitness